1995
DOI: 10.5032/jae.1995.02036
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Learning Styles And Levels Of Cognition Of Instruction Of Horticulture Teachers

Abstract: The flexibility for learners to learn begins with the teacher's style of learning and the levels of cognition utilized in the classroom. Teachers have the basic capability to learn and teach; however, they are not all able to learn and teach effectively in the same exact way. The current study sought to determine the learning style and cognitive level of instruction of central Ohio horticulture teachers. The Florida Taxonomy of Cognitive Behaviors (FTCB) and the Group Embedded Figures Test (GEFT) were used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Several researchers in agricultural education have used the Group Embedded Figures Test (GEFT) to assess students' preferred learning style (Cano & Garton, 1994;Cano & Metzger, 1995;Dyer & Osborne, 1996;Garton et al (1999). The GEFT classifies learners as fielddependent or field-independent, where fielddependent learners focus on the social environment and struggle with problem solving and field-independent learners prefer to perform activities independently and excel in solving problems (Oltman, Raskin, & Witkin, 1971).…”
mentioning
confidence: 99%
“…Several researchers in agricultural education have used the Group Embedded Figures Test (GEFT) to assess students' preferred learning style (Cano & Garton, 1994;Cano & Metzger, 1995;Dyer & Osborne, 1996;Garton et al (1999). The GEFT classifies learners as fielddependent or field-independent, where fielddependent learners focus on the social environment and struggle with problem solving and field-independent learners prefer to perform activities independently and excel in solving problems (Oltman, Raskin, & Witkin, 1971).…”
mentioning
confidence: 99%
“…Several studies (Cano et al, 1992;Raven, et al, 1993;Torres and Cano, 1994;Cano and Metzger, 1995;Miller, 1995;Whittington and Raven, 1995) have been conducted with the primary aim of describing the learning styles of a particular population of agricultural learners. Most of these studies imply that knowledge of learning styles may be used by teachers to improve instruction.…”
Section: Resultsmentioning
confidence: 99%
“…Relevant to agricultural education, researchers (Raven, Cano, Garton, & Shelhamer, 1993;C a n o & Garton, 1994;Whittington & Raven, 1995;Cano & Metzger, 1995) have studied the learning styles of teachers and preservice teachers of agricultural education. The studies concluded that teachers of agriculture differed in learning styles, personality styles, and preferred ways of teaching.…”
mentioning
confidence: 99%